Изучение элементов технологии возделывания картофеля в зоне Полесья Украины - Голуб, Сергій Миколайович; Голуб, Валентина Олександрівна; Голуб, Геннадій Сергійович; Holub, Serhii M.; Holub, Valentyna O.; Holub, Hennadii S. (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования «Рязанский государственный агротехнологический университет имени П.А. Костычева», 2015)
The elements of intensive technology of growing of potato were studied in work, namely the use of different forms and doses of fertilizers for the increase of the productivity and quality of tubers of potato of Sante and Polana sorts in the conditions of western Polyssia of Ukraine in soddy podsolic soils. In order to obtain pure products radioactively potato tubers relatively cesium-137 on sod-podzolic medium secured mobile forms of potassium and phosphorus soils with slightly acidic soil solution and the density of contamination with radioactive cesium 1.9 Ki/sq.km inappropriate to make a double dose of potassium fertilizers in relation to the recommended.
Keywords: fertilizers; productivity; quality; soil; ground; biological products